A new architecture for dynamic e-business database interoperability - Hussain, Omar; Soh, B. (IEEE, 2004)
There have been many approaches of data sharing in e-businesses, attempting at mapping each field at the source to its corresponding field at the target. These approaches eliminate the need for deriving the global schema and hence eliminate a substantial overhead. But, the approaches work out well only when both the source and the target databases have approximately the same content. Moreover, if some concepts of source do not have the counterpart fields in the target then the mapping will lose the concepts. This problem will be further aggregated by the mapping compositions and the large size of the databases. In this paper, we propose a framework to alleviate the interoperability problem.